Transnational Encounters in Early Modern Drama, 1450-1750 - Bloemendal, Jan,; Wouters, Dinah, (Drama and Theatre in Early Modern Europe ;, 2025)
In this volume you will find contributions on transnational European drama of the early modern period, featuring a range of innovative approaches. The volume, for the first time, covers dramas and theatre plays in Latin, English, French, Polish, Dutch, and Spanish. A second innovation is its combination of literary historical research and digital humanities. The topics range from court ballets to the reception of Seneca, from visual evidence of commedia dell'arte performances to the use of onomastics to trace connections between plays, and from TEI-tagging to the creation of Wikidata pages and digital networks on the role of the scheming slave in ancient and early modern Europe. Contributors include: Michał Bajer and Piotr Urbanski, Radhika Koul, Linda Simonis, Nigel Smith, Gabriela Villanueva Noriega, Barbara Fuchs, Thom Pritchard, M.A. Katritzky, Justyna Łukaszewska-Haberkowa, Ioana Galleron, Neven Jovanović, Julia Beine, James A. Parente, Jr.